2014
DOI: 10.1002/chem.201304317
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Solvent Effect on the Nuclearity of Neutral Titanium(IV)‐Based Helicate Assemblies

Abstract: The spontaneous self-assembly of a neutral circular trinuclear Ti(IV) -based helicate is described through the reaction of titanium(IV) isopropoxide with a rationally designed tetraphenolic ligand. The trimeric ring helicate was obtained after diffusion of n-pentane into a solution with dichloromethane. The circular helicate has been characterized by using single-crystal X-ray diffraction study, (13) C CP-MAS NMR and (1) H NMR DOSY solution spectroscopic, and positive electrospray ionization mass-spectrometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 91 publications
1
26
1
1
Order By: Relevance
“…The selection of these building blocks to pre‐program the formation of a helicate‐type structure was motivated by the following facts: 1) It has been shown that the pro‐ligand LH 4 in presence of [Ti(O i Pr) 4 ] generates either a double‐stranded dinuclear helicate or a circular trinuclear helicate ([Ti 3 (L) 3 (HO i Pr) 6 ]) in solid‐state depending on the solvent medium used to isolate the species. Interestingly, the spontaneous rearrangement of the circular species into double‐stranded architecture was observed in solution 9. 2) A novel family of heteroleptic monomeric octahedral TiO 4 N 2 complexes with well‐defined geometries was recently developed: these complexes incorporate two phenyl‐substituted biphenolate ligands and one nitrogenated bidentate chelate 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of these building blocks to pre‐program the formation of a helicate‐type structure was motivated by the following facts: 1) It has been shown that the pro‐ligand LH 4 in presence of [Ti(O i Pr) 4 ] generates either a double‐stranded dinuclear helicate or a circular trinuclear helicate ([Ti 3 (L) 3 (HO i Pr) 6 ]) in solid‐state depending on the solvent medium used to isolate the species. Interestingly, the spontaneous rearrangement of the circular species into double‐stranded architecture was observed in solution 9. 2) A novel family of heteroleptic monomeric octahedral TiO 4 N 2 complexes with well‐defined geometries was recently developed: these complexes incorporate two phenyl‐substituted biphenolate ligands and one nitrogenated bidentate chelate 10.…”
Section: Resultsmentioning
confidence: 99%
“…[15] This observation definitively confirms the structural stability of the complex in solution, whereas for the recently reported [Ti 3 (L) 3 (HOiPr) 6 ] helicate, a spontaneous transformation into a dinuclear helicate was characterized upon dissolution. [9] The bowl shape of [Ti 3 (L) 3 (bpym) 3 ] explains the four doublet of doublets resonance of the bpym proton Ha a , Ha b , Ha c , Ha d as observed in the 1 H NMR spectrum (Figure 3 B). By 1 H NMR spectroscopy, we also notice the absence of interaction between the toluene molecules and the helicate in solution, probably owing to the replacement of toluene by more polar chloroform molecules.…”
Section: (Bpym) 3 ] Complexmentioning
confidence: 88%
See 1 more Smart Citation
“…而 61 与 Ti 4+ 配位后在二氯甲烷与正戊烷中扩散则形成三 核的环状螺旋结构, Ti 4+ 分别与两个配体分子上的四个 酚基 O 原子及两个异丙氧基形成八面体型配位. 此外, 在二氯甲烷溶液中环状螺旋结构还可以转化为双核的 双螺旋结构 [108] . 61 还可以与半径更大的 Zr 4+ 络合, 在乙 醚及二氯甲烷溶液中形成四核的三螺旋结构 [110] .…”
Section: 含氮含氧配体形成的三螺旋unclassified
“…Organometallic and coordination titanium(IV) compounds are of interest due to their reactivity and uses including as reagents for catalytic enantioselective processes [1], organic transformations [2], as initiators for polymerization reactions [3], polymerisation catalysts [4][5][6][7][8][9][10] to metal organic frameworks [11][12][13] and metallo-supramolecular chemistry [14][15][16][17][18][19]. Other applications include the use of alkoxides or aryloxides precursors for the generation of titaniumbased materials [20][21][22][23][24][25][26] and their uses as photo-sensitisers and photo-catalysts [27,28], titaniumbased drugs [29][30][31][32][33][34][35][36][37][38][39] and cell imaging [40][41].…”
Section: Introductionmentioning
confidence: 99%